Son of the morning : a novel - Emezi, Akwaeke (Avon, an imprint of HarperCollinsPublishers, 2025)
Galilee Kincaid has always felt different--haunted by a mysterious secret about her existence--until she meets Lucifer Helel, a powerful being guarding an ancient artifact. As forbidden attraction ignites between them, Galilee discovers her own extraordinary nature, thrusting her into a deadly struggle between Hell, Heaven, and her own family's secrets. Caught between desire, loyalty, and destiny, she must embrace her power--or risk catastrophic consequences for everyone she loves.